Analisis Kinerja Keuangan Bank Victoria Syariah Dengan Pendekatan Metode Rgec - Fatin Najwa Nazurah; Wardatus Syarifah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Health Bank is a very important thing in a financial institution to increase public confidence because a healthy bank will be easy to do its business with normal. Besides, public confidence can convince that the bank is a safe place to store its assets. This research is aimed at determining the health level of Victoria Syariah Bank. This study uses a quantitative descriptive approach. The analytical technique used is the RGEC ratio analysis. Research shows that the financial performance of Bank Victoria Syariah 2017- 2021 measured using the RGEC Method. Risk Profile Foctors assessed through NPF from 2017-2021 with a pretty healthy category, and FDR from 2017-2021 with a very healthy category. The Good Corporate Governance Bank Victoria Syariah factor has fallen into a healthy category. The Earning factor whose assessment consists of ROA from 2017-2021 with a relatively healthy category, ROE from 2017-2021 with a poor category, and BOPO has always experienced a decline with an unhealthy category. and the capital factor in the CAR ratio is always rising every year with very healthy ranks. Where Victoria Corporate Bank can maintain its financial performance from 2017-2020 with the category "Pretty Healthy" but there will be a decline in 2021 with the category "Less Healthy" due to an increase in the NPF ratio of Victoria Corporate Bank of 9.54%.